Minimnya Partisipasi Bermakna Guru dalam Perumusan Kebijakan Pendidikan - Putri, Syafana Azelita Putri; Age Larasati, Diyas; Putri Amelia, Hikmah; Billa Intan Romadona, Syal Sa; Larasti, Gandes; Navis Roihan Daru Noorwinanda, Muhammad (Indo-MathEdu Intellectuals Journal, 2025)
This study discusses that various problems, including those faced by teachers and the education system as a whole, are caused by low participation in determining education policy. The quality of education depends on teachers, irrelevant curricula, uneven distribution of teachers, and excessive administrative burdens hinder teachers' work. This study aims to describe the challenges of education and education policy. The study uses a descriptive qualitative approach with a library research method whose data comes from various sources of articles in electronic journals based on Google Scholar data. The data analysis stages are carried out starting from article collection, article reduction, article display, discussion, and conclusions. The study shows that the limited number of teachers and qualifications impacts the quality of learning in remote areas. Strategic approaches are needed such as including training programs and incentives to improve education services. The Total Quality Management (TQM) approach is a strategy to improve the quality of education. TQM prioritizes the active participation of every member of the organization in continuous quality improvement through strong collaboration, continuous process development, and a focus on customer satisfaction. In education, the main consumers are students, parents, and the community, and the focus of improvement must be on their needs